Evaluation of cerebrovascular reserve in patients with cerebrovascular diseases using resting-state MRI: a feasibility study - Taneja, Kamil (Magn Reson Imaging, 2019)
PURPOSE: To demonstrate the feasibility of mapping cerebrovascular reactivity (CVR) using resting-state functional MRI (fMRI) data without gas or other challenges in patients with cerebrovascular diseases and to show that brain regions affected by the diseases have diminished vascular reactivity. MATERIALS AND METHODS: Two sub-studies were performed on patients with stroke and Moyamoya disease. In Study 1, 20 stroke patients (56.3±9.7 years, 7 females) were enrolled and resting-state blood-oxygenation-level-dependent (rs-BOLD) fMRI data were collected, from which CVR maps were computed. CVR values were compared across lesion, perilesional and control ROIs defined on anatomic images. Reproducibility of the CVR measurement was tested in 6 patients with follow-up scans. In Study 2, rs-BOLD fMRI and dynamic susceptibility contrast (DSC) MRI scans were collected in 5 patients with Moyamoya disease (32.4±8.2 years, 4 females). Cerebral blood flow (CBF), cerebral blood volume (CBV), and time-to-peak (TTP) maps were obtained from the DSC MRI data. CVR values were compared between stenotic brain regions and control regions perfused by non-stenotic arteries. RESULTS: In stroke patients, lesion CVR (0.250 ± 0.055 relative unit (r.u.)) was lower than control CVR (0.731±0.088 r.u., p=0.0002). CVR was also lower in the perilesional regions in a graded manner (perilesion 1 CVR = 0.422±0.051 r.u., perilesion 2 CVR = 0.492±0.046 r.u.), relative to that in the control regions (p = 0.005 and 0.036, respectively). In the repeatability analysis, a strong correlation was observed between lesion CVR (r(2)=0.91, p=0.006) measured at two time points, as well as between control CVR (r(2)=0.79, p=0.036) at two time points. In Moyamoya patients, CVR in the perfusion deficit regions delineated by DSC TTP maps (0.178±0.189 r.u.) was lower than that in the control regions (0.868±0.214 r.u., p=0.013). Furthermore, the extent of reduction in CVR was significantly correlated with the extent of lengthening in TTP (r(2)=0.91, p=0.033). CONCLUSION: Our findings suggested that rs-BOLD data can be used to reproducibly evaluate CVR in patients with cerebrovascular diseases without the use of any vasoactive challenges.